'Individual and connected': an exploration of young people's discourses about youth cafes in Ireland. (14th September 2018) - Moran, Lisa; Brady, Bernadine; Forkan, Cormac; Coen, Liam
ABSTRACT: Since 2000, youth cafes are accorded prominence in Irish youth policies and research. Youth cafes are drug and alcohol free recreational spaces and research shows that they impact positively on young people. Youth cafes are broadly similar to youth clubs, but they are less structured and are primarily youth-led spaces. This paper draws on qualitative materials from a national study of youth cafes in Ireland, arguing that young people's perceptions of youth cafes are linked to individuality and connectedness. In this paper, we explore these discourses surrounding individuality and connection in detail and argue that youth work in the twenty-first century must simultaneously appeal to young people's need for space to 'be' and to find themselves and provide a structure within which they can relate to others and wider society.